Making energy efficiency pro-poor: insights from behavioural economics for policy design - Babette Never (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
This paper reviews the current state of behavioural economics and its applications to energy efficiency in developing countries. Taking energy efficient lighting in Ghana, Uganda and Rwanda as empirical examples, this paper develops hypotheses on how behavioural factors can improve energy efficiency policies directed towards poor populations. The key argument is that different types of affordability exist that are influenced by behavioural factors to varying degrees. Using a qualitative approach, this paper finds that social preferences, framing and innovative financing solutions that acknowledge people's mental accounts can provide useful starting points. Behavioural levers are only likely to work in a policy package that addresses wider technical, market and institutional barriers to energy efficiency. More research, carefully designed pre-tests and stakeholder debates are required before introducing policies based on behavioural insights. This is imperative to avoid the dangers of nudging.
Keywords: 330; Armut und Ungleichheit; Energie